PROFIL KEMAMPUAN LITERASI SAINS (SCIENTIFIC LITERACY) SISWA KELAS X SMA YPK DIASPORA KOTARAJA, PAPUA - Hanida Listiani; Suriyah Satar; Nurbaya Nurbaya; Maik Akobiarek (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to identify the scientific literacy abilities of class X students at SMA YPK Diaspora Kotaraja, Jayapura City, Papua. The research method used in this research is a quantitative descriptive method to describe and map the initial scientific literacy abilities of YPK Diaspora Kotaraja High School students. The population used in this research were all class X students of SMA YPK Diaspora Kotaraja. The sample in this study consisted of 34 class X students using a random cluster sampling technique (cluster sampling). Quantitative data in this research will be obtained using the NoSLiT test instrument developed by Wenning (2006). The data obtained was then analyzed descriptively. The research results show that the scientific literacy abilities of YPK Diaspora Kotaraja High School students are in the low category. If reviewed based on the six NoSLiT indicators, two indicators are in the very low category, namely scientific naming, process skills ability. Three indicators are in the low category, namely the indicators of scientific postulates, main misconceptions about science and scientific disposition. One other indicator is in the medium category, namely the indicator for the rules of scientific evidence. Based on these results, it is necessary to consistently apply scientific literacy in learning so that 21st century skills can be improved and become the foundation for students to build the nation in the future.